Lateral lymph node dissection in rectal cancer: State of the art review. Issue 11 (November 2022) - Hazen, S.J.A.; Sluckin, T.C.; Konishi, T.; Kusters, M.
Abstract: Half of the local regional recurrences from rectal cancer are nowadays located in the lateral compartments, most likely due to lateral lymph node (LLN) metastases. There is evidence that a lateral lymph node dissection (LLND) can lower the lateral local recurrence rate. An LLND without neoadjuvant (chemo)radiotherapy in patients with or without suspected LLN metastases has been the standard of care in the East, while Western surgeons believed LLN metastases to be cured by neoadjuvant treatment and total mesorectal excision (TME) only. An LLND in patients without enlarged LLNs might result in overtreatment with low rates of pathological LLNs, but in patients with enlarged LLNs who are treated with (C)RT and TME only, the risk of a lateral local recurrence significantly increases to 20%. Certain Eastern and Western centers are increasingly performing a selective LLND after neoadjuvant treatment in the presence of suspicious LLNs due to new scientific insights, but (inter)national consensus on the indication and surgical approach of LLND is lacking. An LLND is an anatomically challenging procedure with intraoperative risks such as bleeding and postoperative morbidity. It is therefore essential to carefully select the patients who will benefit from this procedure and where possible to perform the LLND in a minimally invasive manner to limit these risks. This review gives an overview of the current evidence of the assessment of LLNs, the indications for LLND, the surgical technique, pitfalls in performing this procedure and the future studies are discussed, aiming to contribute to more (inter)national consensus.